Analysis of The Role of Indonesia’s Parliamentary Diplomacy in Supporting Palestinian Independence in 2023–2024 - Kusuma Putra, Naufal Ksatria; Kamaludin, Asep (Department of International Relations, Hasanuddin University, 2026)
This study aims to analyze the role of Indonesian parliamentary diplomacy through the Indonesian House of Representatives' Special Committee on Foreign Affairs (BKSAP) in advocating for the Palestinian issue during the 2023–2024 period, especially after the escalation of violence in Gaza following October 7, 2023. Using qualitative methods with a document study approach, interviews, and analysis of BKSAP activities in multilateral and bilateral forums, this study examines Indonesia's strategies in the IPU, APA, and PUIC, as well as bilateral coordination through the Indonesia–Palestine GKSB. The results show that BKSAP played a strategic role by pushing for an emergency item at the IPU, forming the APA Committee on Palestine, and leading strong advocacy at the PUIC until it was elected as the 19th President of the PUIC. At the bilateral level, BKSAP strengthened communication with the PLO/PNC and developed humanitarian cooperation. These findings confirm that Indonesian parliamentary diplomacy has evolved from a symbolic role to become a substantive, flexible, and influential advocacy actor in international humanitarian issues.